Research and implementation of intelligent endogenous technology for SDN cooperative controller - Le ZHANG; Yanqin WU; Ke ZHANG; Dongfeng MAO; Song JIANG; Huawei HU (Dianxin kexue)
In the face of new demands and challenges such as business diversification, data quantification and cloud network integration, the ideas and methods of cloud network operation are changing.As the core capability of the new generation of cloud network operation system, SDN controller was deeply integrated with artificial intelligence technology.The key technologies and application practices of full-process closed-loop autonomy capability including intention analysis, cloud network intelligence perception, guarantee, optimization and automatic execution were studied to form intelligent endogenous capability of SDN controller.Firstly, the SDN controller intelligent endogenous development background and significance were clarified.And then, the ability of intelligent endogenous architecture and distribution of core competence were illustrated, which gradually form the whole process of the closed loop cloud network autonomy.Finally, focusing on 5G slice, SRv6 scene of new technology new business use cases, the intelligent perception, independent guarantee, automatic optimization of the key aspects of technology, and the effect of implementation and application were resolved.Through capability architecture design, key capability research and development, implementation verification and layout in standardization, the internal intelligence of SDN controller would gradually mature and enable smart operation of cloud network.